La quiebra y la extinción de los contratos: algunas reflexiones sobre la incidencia del Código Civil y Comercial (Nueva Epoca, 2020)
Despite the fact that the Civil and Commercial Code was created under the premise of not reforming special private law statutes, a quick tour of its rules reveals a large number of provisions that affect, among others, bankruptcy law. In particular, we focus on the analysis of bankruptcy modifications as a cause for termination of contracts. The specific provisions and their asymmetries with respect to the specific legislation are reviewed. In turn, some other manifestations ofrethinking are identified in the insolvency treatment rules contained in the common regulations.
Keywords: Civil and Commercial Code; Contracts; Bankruptcy; Insolvency; Bankruptcy act